Fear of Missing Out (FOMO), Literasi Keuangan, dan Intensitas Media Sosial Terhadap Keputusan Investasi Mahasiswa Manajemen Keuangan Universitas Islam Kadiri Kota Kediri - Shalumita, Nurshawa Fitri; Mubarrok, Ujang Syahrul (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to examine the influence of psychological factors Fear of Missing Out (FOMO), financial literacy, and social media usage on stock investment decisions among Financial Management students at the Islamic University of Kadiri (UNISKA), Kediri. Using a quantitative survey method, data from 60 students were analyzed through multiple linear regression. Results indicate that FOMO and financial literacy have a positive and significant impact on investment decisions, while social media intensity does not show a significant partial effect. The findings highlight the importance of psychological motivation and financial knowledge in investment behavior, with social media having an indirect influence.